Season-Long Changes in the Body Composition Profiles of Competitive Female Rugby Union Players Assessed via Dual Energy X-Ray Absorptiometry. Issue 3 (3rd July 2022) - Curtis, C.; Arjomandkhah, N.; Cooke, C.; Ranchordas, M. K.; Russell, M.
ABSTRACT: Background : Reference data for the body composition values of female athletes are limited to very few sports, with female Rugby Union players having mostly been omitted from such analyses.Methods : Using dual energy X-ray absorptiometry (DXA) scans, this study assessed the body composition profiles (body mass, bone mineral content; BMC, fat mass; FM, lean mass; LM, bone mineral density; BMD) of 15 competitive female Rugby Union players before and after the 2018/19 competitive season. Total competitive match-play minutes were also recorded for each player.Results : Body mass (73.7 ± 9.6 kg vs 74.9 ± 10.2 kg, p ≤ 0.05, d = 0.13) and BMC (3.2 ± 0.4 kg vs 3.3 ± 0.4 kg, p ≤ 0.05, d = 0.15) increased pre- to post-season for all players. Conversely, FM (21.0 ± 8.8 kg), LM (50.7 ± 3.9 kg), and BMD (1.31 ± 0.06 g·cm −2 ) were similar between time-points (all p > .05). Accounting for position, body mass ( r partial(12) = 0.196), FM ( r partial(12) = −0.013), LM ( r partial(12) = 0.351), BMD ( r partial(12) = 0.168) and BMC ( r partial(12) = −0.204) showed no correlation (all p > .05) against match-play minutes.Conclusion : The demands of the competitive season influenced specific body composition indices (i.e., body mass, BMC) in female Rugby Union players; a finding which was unrelated to the number of minutes played in matches. While the causes of such differences remain unclear, practitioners should be cognizant of the body composition changes occurring throughout a female Rugby Union competitive season and, where necessary, consider modifying variables associated with adaptation and recovery accordingly.